(untitled) (Albayan Scientific Journal, 2023)
Thyme (Thymus capitatus (L.) Hoffm & Link) is an endemic wild plant in southern parts of Al-Jabal Al-Akhdar region, Libya. There are five phenotypes (populations or accessions) of thyme that show flower color polymorphism. Difference in flower color among the five phenotypes is due to genetic variation. This study was conducted to determine the pattern of peroxidase isoenzymes in thyme which growing in south parts of Al-Jabal Al-Akhdar . Laves samples of the five Thymus capitatus (L.) Hoffm & Link genotypes (populations) were evaluated for peroxidase isoenzyme system by horizontal starch gel electrophoresis. All five phenotypes had different number and relative mobility of electrophoretic bands. This variability enabled the five phenotypes of Thymus capitatus (L.) Hoffm & Link to be distinguished.